Peasant agriculture between local and global considerations - Strambi, Giuliana (Przegląd Prawa Rolnego, 2021)
This article deals with the issue of so-called peasant agriculture. It will first analyse the draft law “on the protection and valorisation of peasant agriculture” currently under discussion in the Italian Parliament, in particular the definition of the terms “azienda agricola Contadina” (peasant farm) and “agricoltore contadino” (peasant-farmer), while highlighting the arguments put forward by the citizens’ movement that supports the project, and taking into account the international context in which these arguments had matured. In relation to this last aspect, elements of the UN Declaration on the rights of peasants and other people working in rural areas who will be included in the Italian legal system thanks to the law under discussion, will be analysed. The debate around peasant agriculture offers interesting insights not only on the role that non-industrialised and small-scale agriculture plays in achieving objectives of global importance such as food security or the fight against climate change and, more generally, how the challenge of achieving sustainable development posed by the UN with Agenda 2030 is relevant also from the point of view of traditional institutions of Italian agricultural law, such as the “imprenditore agricolo” (agricultural entrepreneur) or “coltivatore diretto” (direct farmer).